Recurrent herpes zoster in the Shingles Prevention Study: Are second episodes caused by the same varicella-zoster virus strain?. Issue 2 (10th January 2020) - Harbecke, Ruth; Jensen, Nancy J.; Depledge, Daniel P.; Johnson, Gary R.; Ashbaugh, Mark E.; Schmid, D. Scott; Breuer, Judith; Levin, Myron J.; Oxman, Michael N.
Abstract: Herpes zoster (HZ) is caused by reactivation of varicella zoster virus (VZV) that established latency in sensory and autonomic neurons during primary infection. In the Shingles Prevention Study (SPS), a large efficacy trial of live attenuated Oka/Merck zoster vaccine (ZVL), PCR-confirmed second episodes of HZ occurred in two of 660 placebo and one of 321 ZVL recipients with documented HZ during a mean follow-up of 3.13 years. An additional two ZVL recipients experienced a second episode of HZ in the Long-Term Persistence Substudy. All episodes of HZ were caused by wild-type VZV. The first and second episodes of HZ occurred in different dermatomes in each of these five participants, with contralateral recurrences in two. Time between first and second episodes ranged from 12 to 28 months. One of the five participants, who was immunocompetent on study enrollment, was immunocompromised at the onset of his first and second episodes of HZ. VZV DNA isolated from rash lesions from the first and second episodes of HZ was used to sequence the full-length VZV genomes. For the unique-sequence regions of the VZV genome, we employed target enrichment of VZV DNA, followed by deep sequencing. For the reiteration regions, we used PCR amplification and Sanger sequencing. Our analysis and comparison of the VZV genomes from the first and second episodes of HZ in each of the five participants indicate that both episodes were caused by the same VZV strain. This is consistent with the extraordinary stability of VZV during the replication phase of varicella and the subsequent establishment of latency in sensory ganglia throughout the body. Our observations also indicate that VZV is stable during the persistence of latency and the subsequent reactivation and replication that results in HZ.